Investigation Of Glenohumeral Internal Rotation Deficit Tendency of Adolescent Female Volleyball Players During Passive and Dynamic Movements - Hande Argunşah (Türk Spor ve Egzersiz Dergisi)
Objectives: This study aims determining the glenohumeral internal rotation deficit tendency of the elite volleyball players non-invasively through measuring passive physiological and active range of motion of the shoulder joint during overhead movements. This study hypothesizes that volleyball players are prone to develop angular differences in dominant and non-dominant shoulders’ range of motion during passive and active movements. Participants and Methods: Twelve age matched adolescent female players (age of 17.6±0.4, BMI of 21.11±1.08 and height of 170.6±1.7cm) performed jump serve, strike of the ball, horizontal internal- external rotation and internal- external rotation movements and group-based data were analyzed. This experimental study collected bilateral kinematic data from both dominant and non-dominant shoulders wirelessly with Xsens MVN. Each movement performed five times and the average value was calculated for each participant. Results: T-test paired sample for means for dominant and non-dominant shoulders results indicated that ROM did not vary during flexion (dominant: 170.2°±4.5; non-dominant: 171.3°±6.1; p=0.086) and Shoulder Horizontal External Rotation was not significantly different (dominant: 92.7°±4.1 non-dominant: 89.3°±6.3 p=0.052). Contrarily significant differences were obtained during Shoulder Horizontal Internal Rotation (dominant: 27.5°±8.3; non-dominant: 36.8°±7.9; p=0.0053), Shoulder Internal Rotation (dominant: 54.3°±9.0; non-dominant: 65.2°±11.2; p=0.0000) and Shoulder External Rotation (dominant: 98.6±2.5 non-dominant: 90.3°±6.36.7, p=0.0032). Conclusion: This study non-invasively determined the differences between dominant and nondominant shoulders’ passive ROM and investigated the dominant shoulder ROM during overhead movements by using a IMU based wearable motion caption system, which allowed kinematic data collection in real environment. The outcome of the investigation can be used as an early-detection technique for GIRD. Future research should determine if these findings are correlated with MR arthrographic imaging observations of posterior capsular thickening.